If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24k + 15 = 0 Reorder the terms: 15 + 24k = 0 Solving 15 + 24k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 24k = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 24k = 0 + -15 24k = 0 + -15 Combine like terms: 0 + -15 = -15 24k = -15 Divide each side by '24'. k = -0.625 Simplifying k = -0.625
| 7(x+6)=6(x-3) | | 3x-11=10x+12 | | x-(x*0.25)-(x*0.3399)=50000 | | 0=16t^2-300t+2000 | | 21d^2-7d=O | | 6x+4y-2x+5y-5x= | | 12x^3-12x-45=0 | | x+.03x=23.6 | | t(n)=4n-2 | | 7(n-1)=-(3+n) | | k^2+5k-9=0 | | y=-1x^2+29x+12 | | 4r-10= | | 770=3x+77 | | x^2+x=-c | | 5.2+1.7n=1.12 | | 2m+k+3m+2k= | | k+1=k^2+k+c | | 3w+14=50 | | k=-2k^2-k | | 8x+7=5x-21 | | 3(p+4)=24 | | 4y+6y-5=10y-5 | | 5k+40L-35m= | | Sqrt(7x+44)=x | | Ix+7I=2 | | 9-7(5x-8)=63-9x | | 6(x+1)=2(3x+1)+4 | | 11x+5-3x+7= | | x^3+4*x^2+-11*x+30=0 | | 15(a)=225 | | 5x+3=7+5x |